Influence of Substituting Dietary Soybean for Air‐Classified Sunflower (Helianthus annuus L.) Meal on Egg Production and Steroid Hormones in Early‐Phase Laying Hens. Issue 1 (18th October 2013) - Laudadio, V; Ceci, E; Nahashon, SN; Introna, M; Lastella, NMB; Tufarelli, V
Contents Soybean meal (SBM) is the most widely and expensive protein source used in the formulation of poultry diets; however, when the price of SBM increases, poultry nutritionists seek alternative sources that are more economical in formulating least‐cost rations. This research aimed to evaluate the effects of dietary air‐classified sunflower meal (SFM) on some productive parameters and plasma steroid hormones in laying hens. In this trial, 20‐week‐old laying hens (ISA Brown strain) in the early phase of production were randomly assigned to two groups and fed wheat middlings‐based diets containing soybean (135 g/kg; 48% CP) or air‐classified SFM (160 g/kg; 41% CP) as the main protein source. Laying performance, egg size and feed conversion ratio were evaluated for 10 week. Plasma steroid hormones (progesterone and oestradiol) in the hens were quantified weekly. Substituting SBM with air‐classified SFM did not change (p > 0.05) the hens' growth performance, whereas feed consumption and efficiency were positively influenced (p < 0.05) by SFM treatment. Egg production rate was improved in hens fed the SFM diet (p < 0.05), as well as the percentage of medium‐size eggs that was higher for SFM treatment (p < 0.05). Steroid hormones levels were affected by dietary treatment (p < 0.01). From our findings, it could be effective to include air‐classified SFM in early‐phase laying hen diets as an alternative protein source substituting SBM, without negative influence on productive performance and egg traits, reducing also the production costs.